Analysis of service quality at Mitra Utama shipping company - Hanif Afadil Darojat (Digital Business: Tren Bisnis Masa Depan, 2023)
This research takes the title "Analysis of Service Quality in Major Partners Expeditionary Service Companies". The purpose of this study was to determine the level of consumer expectations regarding the service quality of the Main Partner Expedition Service Company and the performance of service quality felt by consumers after receiving the services of the Main Partner Expedition Service Company. The population in this study were all consumers of the Main Partner Expedition Service Company. The samples taken in this study are some of the customers who represent all customers of the Main Partner Expedition Service Company. Data analysis in this study used the IPA method. The results of this study are that the majority of respondents rated their expectations or interests regarding the company's service quality in terms of reliability, responsiveness, assurance, empathy, and tangible as satisfactory (mean 2.98, located between 2.50 to 3.24), most respondents assessing the performance of the company's service quality in terms of reliability, responsiveness, assurance, empathy, and tangible is very important (mean 3.32 lies between 3.25 to 4.00) and the majority of respondents assess the performance and expectations of the company's service quality reviewed from the aspects of reliability, responsiveness, assurance, empathy, and tangible, it has satisfied consumers because the conformity value is 111.41> 100%.